Diagnosis and Therapeutic Management of Trypanosoma evansi in an American Bully with Corneal Opacity - R Patel, Bhavika; Kumar, Binod; K Patbandha, Tapas; Vasava, Amrita; S Prajapati, Ankit (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Trypanosomosis is a haemoprotozoan infection, caused by  different members of Trypanosoma species. It is widely  dispersed form of animal trypanosomosis that is harmful,  affecting various domestic and wild animal species (Eloy and  Lucheis, 2009). Most of the time, the parasite is mechanically  transmitted by biting flies like Tabanus, Stomoxes, Tsetse  and Culicoides (Green, 2006). Canine trypanosomosis varies  in severity from acute to subacute and chronic form. Dogs  are frequently affected by an acute and severe form, which  may result in death within two to four weeks (Soulsby,  1982). The clinical manifestations of canine trypanosomosis  include weight loss, growing weakness, anorexia, anaemia,  intermittent fever, conjunctivitis, swelling of the head, throat  and limbs, staggering gait, enlarged superficial lymph nodes,  difficulty in swallowing and corneal opacity due to strong  reactions from the immune system (Kumar et al., 2020). One  of the main symptoms of this condition is anaemia, which  is caused by the mononuclear phagocytic system expelling  red blood cells from the bloodstream. After an infection  lasting several months, anaemia may recover to varying  degrees when the parasitaemia becomes low and sporadic  (Urquhart et al., 2002). The World Animal Health Organization  currently classifies T. evansi as a multi-species illness and a  zoonotic disease, following the clinical case reports of human  trypanosomosis in Egypt and India (Aregawi et al., 2019). A single dose of diminazene aceturate is sufficient  to eradicate a trypanosomosis infection in dog (Agrawal  et al., 2020); however there are several more efficient  trypanosomacidal medicines for dogs, such as suramin  and quinapyramine (Rani and Suresh, 2007). Giving  diminazene diaceturate to dogs at a dose rate higher  than 3.5 mg/kg body weight is deemed lethal (Han et al.,  2014). In India, the occurrence of canine trypanosomosis is  sporadic in nature (Behera et al., 2017). However, no report  on canine trypanosomosis with ophthalmic involvement  has been reported in western India in particular Gujarat.  Therefore, the present case report documents on the  clinical presentations, diagnosis, haemato-biochemistry and  therapeutic management of trypanosomosis in an American  bully dog from Gujarat.
Keywords: weakness; various domestic; infection; medicines for dogs; red blood cells